2011
DOI: 10.1364/oe.19.001824
|View full text |Cite
|
Sign up to set email alerts
|

Effects of site substitutions and concentration on upconversion luminescence of Er^3+-doped perovskite titanate

Abstract: References and links properties of BaTiO3 and SrTiO3 nanoparticles," J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
105
3
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 156 publications
(118 citation statements)
references
References 20 publications
7
105
3
3
Order By: Relevance
“…In our experiment, the optimal doping concentration, for the green emission, is x = 0.1, whereas for the red one it is over 0.46 mol, which is much higher than that in other perovskite hosts (most of them below 0.01 mol 41 ). The high concentration of Er 3+ ions can increase the ions number of absorbing pumping source and promote the energy transfer between neighboring Er 3+ ions excited to intermediate energy level, which is important to get higher upconversion efficiency when excited by 980 nm laser.…”
Section: B Upconversion Emission Propertiesmentioning
confidence: 53%
See 2 more Smart Citations
“…In our experiment, the optimal doping concentration, for the green emission, is x = 0.1, whereas for the red one it is over 0.46 mol, which is much higher than that in other perovskite hosts (most of them below 0.01 mol 41 ). The high concentration of Er 3+ ions can increase the ions number of absorbing pumping source and promote the energy transfer between neighboring Er 3+ ions excited to intermediate energy level, which is important to get higher upconversion efficiency when excited by 980 nm laser.…”
Section: B Upconversion Emission Propertiesmentioning
confidence: 53%
“…[27][28][29] Oxide materials are usually chemically, mechanically, and thermally stable, and therefore can be promising hosts for light UC applications. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] For these purposes, Er doped many oxide hosts UC materials have been designed and prepared, such as ZnO, 27 43 and NaNbO 3 44 have been studied. However, these types of pervoskite oxides have chemical and physical stability but low emission efficiency due to their low solubility of trivalent rare earth ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 We have previously observed that the temperature dependence of UC emission in Er 3þ -doped BTO powders is associated with phase transitions of BTO host. 18 Recently, we have presented an approach to enhance and modulate UC emission through applying a relatively low bias voltage to the Ln 3þ -doped BTO thin film. 19 The realization of UC emission in Ln 3þ -doped ferroelectric materials provides us an opportunity to develop a class of "smart" materials with luminescence properties that change in response to external stimuli including electric field, mechanical force, temperature, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with previous studies. 18,20 Figure 2 displays the UC luminescence spectra of BTO:Ln 3þ phosphors doped with (a) 2%Yb 3þ , 0.2%Tm 3þ ; (b) 2%Yb 3þ , 0.1%Er 3þ , and 0.2%Tm 3þ ; (c) 5%Yb 3þ , 0.1%Er 3þ , and 0.2%Tm 3þ ; (d) 5%Yb 3þ , 0.02%Er 3þ , 0.2%Tm 3þ , respectively. Figure 2(a) shows the UC emission spectrum of the BTO:2%Yb 3þ , 0.2%Tm 3þ sample.…”
Section: Introductionunclassified